2013
DOI: 10.12669/pjms.292.2981
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of gestational choriocarcinoma and massive ascites by hypothermic intraperitoneal perfusion chemotherapy guided by ultrasound followed by cytoreductive surgery

Abstract: A 33-year-old woman with very poor health status was admitted to our hospital because she had experienced increasing abdominal distention for three months, CT examination showed a right ovarian tumor together with massive abdominal and pelvic fluid. The patient was first treated by continuous circulatory hypothermic intraperitoneal perfusion chemotherapy (HIPC) guided by B-mode ultrasound, followed by cytoreductive surgery (CRS) after her ascites was controlled and her health condition improved. She was diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Some studies demonstrated that this synergism between various cytotoxic drugs and hyperthermia is stronger at temperatures >39°C. On the other hand, the rate of small bowel heat injury increases above 43°C in humans, while HIPEC at ≤43°C appears to not influence the complication rate of HIPEC (11,24). The longer the peritoneal cavity temperature remains near 43°C, the stronger the synergism between cytotoxic drugs and hyperthermia.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Some studies demonstrated that this synergism between various cytotoxic drugs and hyperthermia is stronger at temperatures >39°C. On the other hand, the rate of small bowel heat injury increases above 43°C in humans, while HIPEC at ≤43°C appears to not influence the complication rate of HIPEC (11,24). The longer the peritoneal cavity temperature remains near 43°C, the stronger the synergism between cytotoxic drugs and hyperthermia.…”
Section: Discussionmentioning
confidence: 97%
“…The toxic effects of anticancer drugs were graded according to the National Cancer Institute Common Toxicity Criteria for Adverse Events (CTCAE) Version4.0. Effectiveness was evaluated based on ascites remission according to our previous modification of the World Health Organization criteria (22)(23)(24)(25)(26). Calculation of the total objective remission rate (ORR) was based on the remission of ascites 4 weeks after the completion of HIPEC (23).…”
Section: Outcomes and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat control methods (instantaneous heating) using temperature monitoring and control in HIPEC surgery include hot water and microwave (or high-frequency induction local heating thermal treatment) heating [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. These methods suffer from low precision and unstable perfusion rate during temperature control [ 27 ].…”
Section: Discussionmentioning
confidence: 99%